The Role of Ghuruh Alep In Instilling Islamic Values In Early Childhood: Towards Child-Friendly And Islamic-Oriented Formal Education - Moh. Abdan Syakuro; Reswari, Ardhana; Danang Prastyo; Lisa Apriliyana (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Ghuruh Alep, the pioneer in teaching the Arabic alphabet found in the Qur'an to children or students, plays a crucial role in instilling Islamic values in early childhood. This qualitative case study aims to describe Ghuruh Alep role in planting Islamic values in young children. The analysis focuses on Quranic verses as a perspective to understand Ghuruh Alep role. The research is conducted at Mushalla Nurul Islam in the village of Karduluk, Sumenep Regency. The informants include one teacher, three parents of students, and five students from Mushalla Nurul Islam. The findings reveal that Ghuruh Alep holds a key role in imparting religious values to young children. Through a careful approach, he introduces the Arabic alphabet until students can read the Qur'an. Guidance in worship, moral education, affection, positive examples, and wise advice are central to his approach. Ghuruh Alep ensures progression from desired behaviors to moral principles and cognitive maturity before teaching abstract concepts. This article highlights the significance of Ghuruh Alep role in shaping religious values, emphasizing adaptation to the changing times.